THE EFFECT OF USING GOOGLE SITES MEDIA ON THE LEARNING OUTCOMES OF SCIENCE AND TECHNOLOGY STUDENTS IN GRADE V - Nadya Jihan Nabilah; Zulfa Dewina (Universitas Majalengka, 2023)
Learning media is very influential in teaching and learning activities to achieve learning objectives. Besides teaching, the teacher acts as a facilitator who is expected to be able to present innovative learning media for students. The teacher's creativity in choosing learning media can attract students' learning interests so that it has an impact on improving learning outcomes. This study aims to determine and analyze the use of instructional media Google Sites on the learning outcomes of grade 5 students in the subject of Natural Sciences (IPA) at SDN Beji Timur. The research method used is like an experimentwithNon-equivalent Control Group Design. The population in this study were all 5th-grade students at SDN Beji Timur for the 2022/2023 academic year. In contrast, the research sample was 68 students consisting of 34 students in class 5B and 34 in class 5E. The type of instrument used in this study was a multiple choice test that was tested whenPre-test andPost-test. Data analysis techniques were carried out to test normality by testingKolmogorov-Smirnov, homogeneity test with Levene Statistic. Next, test the hypothesis using the test independent sample t-test. Based on the t-test, hypothesis testing shows no effect on the average grade 5 science learning outcomes using mediaGoogle Sites at SDN Beji Timur. Thus, using mediaGoogle Sites does not affect student learning outcomes in Natural Sciences (IPA) subjects at SDN Beji Timur. Demi tercapainya tujuan pembelajaran, media pembelajaran sangat berpengaruh dalam kegiatan belajar mengajar. Disamping mengajar, guru berperan sebagai fasilitator yang diharapkan mampu menghadirkan media pembelajaran yang inovatif bagi siswa. Kreativitas guru dalam memilih media pembelajaran dapat menarik minat belajar siswa sehingga berdampak pada peningkatan hasil belajarnya. Penelitian ini bertujuan untuk mengetahui dan menganalisis penggunaan media pembelajaran Google Sites terhadap hasil belajar siswa kelas 5 pada mata pelajaran Ilmu Pengetahuan Alam (IPA) di SDN Beji Timur. Metode penelitian yang digunakan adalah Quasi Experiment dengan Non-equivalent Control Group Design. Populasi dalam penelitian ini adalah seluruh siswa kelas 5 SDN Beji Timur tahun ajaran 2022/2023. Sedangkan yang dijadikan sampel penelitian adalah 68 siswa yang terdiri dari 34 siswa kelas 5B dan 34 siswa kelas 5E. Jenis instrumen yang digunakan pada penelitian ini adalah tes pilihan ganda yang diujikan saat Pre-test dan Post-test. Teknik analisis data dilakukan untuk menguji normalitas dengan uji Kolmogorov-Smirnov, uji homogenitas dengan Levene Statistic. Selanjutnya, untuk menguji hipotesis menggunakan uji independent sample t-test. Berdasarkan pengujian hipotesis uji-t menunjukkan bahwa tidak ada pengaruh dari rata-rata hasil belajar IPA kelas 5 dengan penggunaan media Google Sites di SDN Beji Timur. Dengan demikian dapat disimpulkan bahwa penggunaan media Google Sites tidak berpengaruh terhadap hasil belajar siswa pada mata pelajaran Ilmu Pengetahuan Alam (IPA) di SDN Beji Timur.